Evaluation of styloid process using digital panoramic radiographs - Manishkumar Shete; Yogita Khalekar; Raghvendra Byakodi (Wolters Kluwer Medknow Publications, 2015)
Context: The styloid process (SP) is an anatomical structure, whose clinical importance is not well understood. Proper clinical and radiographic evaluation can detect an elongated styloid process (ESP) and calcification of the stylohyoid ligament. SP is said to be elongated if it is longer than 3 cm in length. Anatomical variations are very common. It has been reported that 2-28% of the general population show radiographic evidence of mineralization of a portion of the stylohyoid chain. SP could be elongated although symptoms are present only in some individuals. Panoramic radiography is most economical and readily available imaging modality to view the SP bilaterally. Aim: The aim of this present study was to assess the SP on digital panoramic radiographs. Subjects and Methods: The study was conducted on 500 digital panoramic radiographs available as a soft copy in our Radiology Department. These radiographs were taken using a digital panoramic system. The radiographic length of the SP was measured on both sides using the measurement toolbars on the accompanying analysis software. Statistical Analysis Used: The collected data was entered in a spreadsheet (Excel 2007, Microsoft, Richmond, USA) and was analyzed using statistical analysis software (SPSS version 17, Chicago, USA). Results: Average length of SP on the left side was 34.54 ± 7.54 mm and 33.02 ± 6.70 mm in male and female population, respectively. The average length of SP on right side was 35.30 ± 7.46 mm and 34.54 ± 7.31 mm in male and female population, respectively. The length of both styloids increased with age and males had longer styloids than females. Elongated styloids were present in 82.2% of the panoramic radiographs. Langlais type I elongated styloids were more common than others. Conclusions: Panoramic radiography is useful for detection of an ESP and/or ossification of the stylohyoid ligament in patients with or without symptoms and helps to avoid a misdiagnosis of tonsillar pain or pain of dental, pharyngeal, or muscular origin.